Non-scattering wavenumbers and far field invisibility for a finite set of incident/scattering directions. (12th March 2015) - Dhia, Anne-Sophie Bonnet-Ben; Chesnel, Lucas; Nazarov, Sergei A
Abstract: We investigate a time harmonic acoustic scattering problem by a penetrable inclusion with compact support embedded in the free space. We consider cases where an observer can produce incident plane waves and measure the far field pattern of the resulting scattered field only in a finite set of directions. In this context, we say that a wavenumber is a non-scattering wavenumber if the associated relative scattering matrix has a non-trivial kernel. Under certain assumptions on the physical coefficients of the inclusion, we show that the non-scattering wavenumbers form a (possibly empty) discrete set. Then, in a second step, for a given real wavenumber and a given domain, we present a constructive technique to prove that there exist inclusions supported in for which the corresponding relative scattering matrix is null. These inclusions have the important property to be impossible to detect from far field measurements. The approach leads to a numerical algorithm, which is described at the end of the paper and which allows us to provide examples of (approximated) invisible inclusions.